Federative relations and Russia space problems - Leonid Vardomskiy (European Regional Science Association (ERSA), 2014)
Benefits of federation are in more flexible use of the social and economic potential of its subjects at wide inter-regional competition. The federal system allows to use effects of either greater economic space or more complete considering of local conditions and interests. Specificity of modern Russian federalism lies in the history of the formation and organization of its space. Russian history is a history of over-centralized state, which however considered the specificities of individual territories . Introduction of federalism in a state management practices in Russia in early 1990s. occurred in the wave of democratization, but excluding the condition of Russian economy and inherited status of the Russian state space. Strong regions won from the devolution to the RF regions, but it was the result of unequal conditions in which the subjects of the federation were in the market transformation and dissolution of the USSR. Among economic reasons of recentralization in 2000 are growing regional disparity , payments crisis, regional protectionism , the contradictions between the center and the regions about the financial and production assets . In the most critical moment of market transformation economic disintegration of the space of the country began to amplify. Business - elite close to the authorities , seek to free hands in resources development and their export. Request to strengthen the central government came also from the management of economically weak RF subjects who needed financial support from the federal budget. After the restoration of the vertical of power in relations with the regions intergovernmental transfers became the main instrument of the federal government. Huge volume redistribution operations have become a key element of regional policy . Built vertical power was aimed at neutralizing possible political and social consequences of divergence space growth, but not the reasons for its cause. Today federal relations are in a certain accordance with a level of the Russian economy and its spatial structure. The introduction of more democratic forms of federalism without appropriate technological and structural changes in the economy of the RF subjects can create more problems than positive effects. To change the system of power , it is necessary to change a space and the technological base of the economy. Change of the space requires joint efforts of all levels of government and local communities. The task of the central government is to organize their partnership , using political , economic and social institutions .
Keywords: H77; R12; F01; F15; 330; federalism Russia space development competition